2018
DOI: 10.1186/s13601-018-0198-7
|View full text |Cite
|
Sign up to set email alerts
|

The Allergic Rhinitis Clinical Investigator Collaborative (AR-CIC): verification of nasal allergen challenge procedures in a study utilizing an investigational immunotherapy for cat allergy

Abstract: BackgroundThe Allergic Rhinitis Clinical Investigator Collaborative (AR-CIC) is a network of experienced Allergic Rhinitis (AR) researchers developing better research tools based on the nasal allergen challenge (NAC). A key objective of such is the ability to detect efficacy in a small population. AR-CIC sought to test its NAC protocol as a secondary objective in two small mechanistic research trials of a novel form of immunotherapy [Cat Peptide Antigen Desensitisation (Cat-PAD)] for which efficacy had previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Many trials with T‐cell peptides have shown limited efficacy and/or led to nonimmediate allergic reactions during treatment although immunologic effects were demonstrated …”
Section: Current Managementmentioning
confidence: 99%
“…Many trials with T‐cell peptides have shown limited efficacy and/or led to nonimmediate allergic reactions during treatment although immunologic effects were demonstrated …”
Section: Current Managementmentioning
confidence: 99%
“…The Allergic Rhinitis Clinical Investigator Collaborative (AR‐CIC) is a network of experienced AR specialists that are continuously working on improving research tools to analyze data obtained from nasal allergen challenge tests. The network validated the efficacy of the current AR‐CIC nasal allergen challenge procedure of a novel peptide‐based immunotherapy for cat allergy …”
Section: Prevalence Of Allergic Rhinitismentioning
confidence: 83%
“…24 André et al 10 found a weak correlation between obstructive symptoms and minimal crosssectional area, but was there was no relationship in asymptomatic patients. Additionally, Neighbour et al 26 identified only a modest correlation between TNSS and PNIF. Future directions include considering other physiologic measures that may potentially correlate more strongly with PROMs including computational fluid dynamic modeling, nasal mucosal temperature, or humidity of inspired oxygen.…”
Section: Discussionmentioning
confidence: 99%